2015 IEEE International Conference on Industrial Technology (ICIT) 2015
DOI: 10.1109/icit.2015.7125193
|View full text |Cite
|
Sign up to set email alerts
|

Multiphysical modeling for fault detection in Permanent Magnet Synchronous Motors

Abstract: the aim of this paper is to present an analytical multiphysical model of Permanent Magnet Synchronous Motors (PMSMs) dedicated to fault detection purpose. The electromagnetic aspect is based on the analytical calculation of the Maxwell pressure in the air-gap. An existing mechanical approach is improved to compute natural frequencies of the machine taking into account its different parts. A better agreement has been obtained between analytical results and those issued from a Finite Element Analysis (FEA) appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…For this reason, an improved analytical approach has been used to calculate them, taking into account the entire stator structure with teeth and winding [11]. Analytical results have been validated by a Tow-Dimensional (2-D) FEA using ANSYS software, for different circumferential modes.…”
Section: B Mechanical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, an improved analytical approach has been used to calculate them, taking into account the entire stator structure with teeth and winding [11]. Analytical results have been validated by a Tow-Dimensional (2-D) FEA using ANSYS software, for different circumferential modes.…”
Section: B Mechanical Modelmentioning
confidence: 99%
“…A 24-slot four-pole PMSM, with parameters listed in Appendix A in [11], has been used as a reference motor. It is driven by a 3-phase current at constant frequency (50 Hz).…”
Section: B Mechanical Modelmentioning
confidence: 99%
“…Results showed that they demonstrated the accuracy of the method they proposed. Alameh et al [14] carried out studies on the detection of eccentricity faults in PMSMs. They presented an analytical multiphysical model.…”
Section: Eccentricity Faults In Pmsmsmentioning
confidence: 99%